2014
DOI: 10.1371/journal.pone.0108976
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Consistent Condom Use among College Students in China: Application of the Information-Motivation-Behavior Skills (IMB) Model

Abstract: BackgroundDue to the increase incidents of premarital sex and the lack of reproductive health services, college students are at high risk of HIV/AIDS infections in China. This study was designed to examine the predictors of consistency of condom use among college students based on the Information-Motivation-Behavioral Skills (IMB) model and to describe the relationships between the model constructs.MethodsA cross-sectional study was conducted to assess HIV/AIDS related information, motivation, behavioral skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
26
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 36 publications
9
26
0
3
Order By: Relevance
“…Specifically, past studies found that information does not always have a direct effect on sexual risk behavior, but many studies suggest that information remains a necessary component of HIV prevention interventions because of the influence knowledge has on behavioral skills. Our results fit with other studies that found that information significantly predicted behavioral skills, but did not directly predict sexual risk behavior [21–22,24,32,44,4849,54]; however, our results conflict with those that found no effect of information [2528,31,35] and those with a direct relationship with condom use [22,43]. It has been argued that the importance of HIV prevention information may be attenuated within populations with higher levels of knowledge [37], and we found low levels of HIV prevention knowledge within this sample of alcohol-using STI clinic patients providing additional evidence in support of this hypothesis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Specifically, past studies found that information does not always have a direct effect on sexual risk behavior, but many studies suggest that information remains a necessary component of HIV prevention interventions because of the influence knowledge has on behavioral skills. Our results fit with other studies that found that information significantly predicted behavioral skills, but did not directly predict sexual risk behavior [21–22,24,32,44,4849,54]; however, our results conflict with those that found no effect of information [2528,31,35] and those with a direct relationship with condom use [22,43]. It has been argued that the importance of HIV prevention information may be attenuated within populations with higher levels of knowledge [37], and we found low levels of HIV prevention knowledge within this sample of alcohol-using STI clinic patients providing additional evidence in support of this hypothesis.…”
Section: Discussionsupporting
confidence: 91%
“…Our results suggest motivation had a direct effect on behavioral skills, but also had a direct effect on sexual risk behavior. This partial mediation effect of motivation on sexual risk behavior through behavioral skills is consistent with other IMB model research [21,25,2729,31,35,44,54], but conflicts with evidence of a fully-mediating effect [32,36,43,49]. Thus, motivation and behavioral skills remain important components of the IMB model, but some populations may rely more heavily upon behavioral skills to enact protective behavior compared to others.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Theory-based intervention is widely believed to be more likely to effectively change behavior and maintain such behavior change than non-theory-based intervention. Among extant theory and models, the Information-Motivation-Behavioral Skills (IMB) model has received consistent empirical support in the context of HIV prevention among various key populations, including heterosexual people living with HIV [15], sexually transmitted infection (STI) clinic patients [16], female sex workers [17], senior high school students [18,19], college students [20], male street laborers [21], unmarried female migrants [22], and MSM [23].…”
Section: Introductionmentioning
confidence: 99%
“…Desde el modelo IMB, se ha encontrado que es más probable que se protejan y usen el preservativo los hombres con información de cómo protegerse, motivados para usar condón y con las habilidades para hacerlo (Bermúdez, Herencia Leva y Uribe, 2009;Cunill, Gras, Planes y Serda, 2012;Espada, Morales, Guillén, Ballester y Orgilés, 2016;Liu, et al, 2014;Mazo, Domínguez y Cardona, 2014;Uribe, Aguilar, Zacarías y Aguilar, 2015).…”
Section: Introductionunclassified